THE DEVELOPMENT OF THE TOURISM ECONOMY IN POLAND COMPARED TO EUROPE IN 2010–2018 - Ewa Bąk-Filipek; Sharon C. Cobb; Katarzyna Podhorodecka (Acta Scientiarum Polonorum. Oeconomia, 2019)
In article shown the problem with the assessment of the importance of tourism was recognized, and the first initiatives to develop the so-called tourism satellite in the 1990s. The aim of research is to answer the question: what is the share of the tourism economy in generating GDP in Poland and in Europe? The second goal was to answer the question: how has the Polish tourism economy responded to the global economic crisis and has this reaction been similar to European markets? The following hypotheses were adopted: first, the share of the tourism economy in Poland is smaller than the average for Europe, and, second, the Polish tourism economy reacted better to the global economic crisis than other European economies. The article uses data from the satellite tourism account for Poland and World Tourism and Travel Council (WTTC) data showing the multiplier effect of tourism in Europe. The data analysis shows that share of tourism economy in Polish GDP is 6% and the share of tourism industry in Europe in GDP is 8% in the end of second decade of twenty-first century.